ANALYSIS OF THE MAIN ASPECTS AND FACTORS OF THE FORMATION OF EDUCATIONAL PROGRAMS OF SOCIAL ENTREPRENEURSHIP - E. Klushina (Вестник Северо-Кавказского федерального университета, 2022)
This article analyzes aspects of the formation of social entrepreneurship programs at the internal and external levels within the social context. The study focuses on the importance of social entrepreneurship in this study in a general sense and its position in relation to other forms of entrepreneurship today. Trends in the development of entrepreneurial education are considered, and the need for training in social entrepreneurship on the basis of higher educational institutions is proved. Methods and innovative forms of formation of educational programs on social entrepreneurship are described. The differences between teaching traditional entrepreneurship and social entrepreneurship are outlined. The assessment of thee ectiveness of the implementation of entrepreneurial education is carried out. Based on the results of the study, problems were formulated, and a number of measures were proposed to solve them.